2021
DOI: 10.1521/aeap.2021.33.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers’ Knowledge, Attitudes, and Beliefs About HIV Pre-Exposure Prophylaxis (PrEP): Informing Network-Based Interventions

Abstract: Increasing access to pre-exposure prophylaxis (PrEP) in primary care settings for patients who may be at risk for HIV could help to increase PrEP uptake, which has remained low among certain key risk populations. The current study conducted interviews with primary care providers identified from national claims data as having either high or low likelihood of serving PrEP-eligible patients based on their prescribing practices for other sexually transmitted infections. The study yielded important information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Our findings are consistent with three recent studies addressing barriers to PrEP access, including a literature review from 2020 27 and others from 2021 based on interviews with primary care providers across the United States 28 and with women experiencing intimate partner violence and their providers in the Northeast. 29 Specifically, all the barriers to PrEP identified in the current study were identified in at least one of the other studies, with some, such as concerns about side effects and adherence and provider biases or stigma about who is at risk for HIV, being identified by all three studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with three recent studies addressing barriers to PrEP access, including a literature review from 2020 27 and others from 2021 based on interviews with primary care providers across the United States 28 and with women experiencing intimate partner violence and their providers in the Northeast. 29 Specifically, all the barriers to PrEP identified in the current study were identified in at least one of the other studies, with some, such as concerns about side effects and adherence and provider biases or stigma about who is at risk for HIV, being identified by all three studies.…”
Section: Discussionsupporting
confidence: 91%
“…31 Task shifting to non-prescribers in the care team was emphasized in a study of primary care providers' attitudes about PrEP that also identified the importance of integrating PrEP procedures into clinical workflows. 28 Our work therefore reinforces the importance of focusing PrEP implementation strategies on a full range of stakeholders, which aligns with bestpractices in implementation science methods that have been emphasized in the Federal Plan to End the HIV Epidemic. 32…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…TelePrEP may help clients who struggle to find time or transportation to travel to meet the monitoring requirements, especially those living in a PrEP desert [62][63][64]. The PrEP desert status is strongly associated with the Southern US and lower urbanicity where HIV stigma, poverty, and lack of insurance are prevalent [8,9]. TelePrEP in South Carolina, which showed the applicability of telePrEP services in a Southern urban area, is now expanding in Southern rural areas [54].…”
Section: Discussionmentioning
confidence: 99%
“…PCPs having limited experience and knowledge of PrEP is consistent with previous studies and has been shown to serve as a significant barrier to prescribing PrEP to their patients. [36][37][38] Because the likelihood of future PrEP understudied, but has the potential to improve user experience, although staff and cost-effectiveness has not been established. 45 This could be a direction for future implementation to reduce some of the patient-identified logistical and financial barriers related to multiple clinic appointments.…”
Section: Thematic Findingsmentioning
confidence: 99%